Work culture and migrant women's welfare marginalization - Psimmenos, Iordanis (The Greek Review of Social Research, 2007)
<div style="font-size: 11.0413px; font-family: serif; left: 91.4598px; top: 308.957px; transform: rotate(0deg) scale(0.977237, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="381.9042067446709">Central to this paper is the relationship between work and welfare marginalization of <div style="font-size: 11.0413px; font-family: serif; left: 91.46px; top: 324.377px; transform: rotate(0deg) scale(0.912463, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="382.3221667520523">migrant women domestic workers. Based upon the findings of a recent (2005-2007) <div style="font-size: 11.0413px; font-family: serif; left: 91.4594px; top: 339.785px; transform: rotate(0deg) scale(1.08675, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="382.5360067558288">research study on Albanian and Ukrainian domestic workers’ access to social <div style="font-size: 11.0413px; font-family: serif; left: 91.4588px; top: 355.194px; transform: rotate(0deg) scale(0.978648, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="381.86856674404146">insurance, medical and children’s care (i.e. nurseries, kindergartens), the paper claims <div style="font-size: 11.0413px; font-family: serif; left: 91.4582px; top: 370.602px; transform: rotate(0deg) scale(0.959528, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="381.8923267444611">that welfare barriers are constituted around lack of resources, discriminations as well as <div style="font-size: 11.0413px; font-family: serif; left: 91.4577px; top: 386.01px; transform: rotate(0deg) scale(0.955528, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="132.81840234565735">conditions and values at work. <div style="font-size: 11.0413px; font-family: serif; left: 108.461px; top: 401.43px; transform: rotate(0deg) scale(0.920366, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="364.74084644155505">At the highest level of generality, paid domestic work is considered part of an <div style="font-size: 11.0413px; font-family: serif; left: 91.4572px; top: 416.839px; transform: rotate(0deg) scale(0.886972, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="381.93012674512863">economic activity that is increasingly difficult to relate with the official state policies <div style="font-size: 11.0413px; font-family: serif; left: 91.4567px; top: 432.247px; transform: rotate(0deg) scale(1.08569, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="382.16448674926755">and welfare provisions, because of its fluid and personalized work conditions. <div style="font-size: 11.0413px; font-family: serif; left: 91.4561px; top: 447.656px; transform: rotate(0deg) scale(0.963095, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="381.9312067451477">However, the typical processes, routes followed, and set of ideas developed by migrant <div style="font-size: 11.0413px; font-family: serif; left: 91.4555px; top: 463.064px; transform: rotate(0deg) scale(1.04153, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="382.553286756134">women in domestic work in order e.g to maintain employability, necessitate the <div style="font-size: 11.0413px; font-family: serif; left: 91.4557px; top: 478.484px; transform: rotate(0deg) scale(0.961774, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="381.8242867432595">adoption of practices and values which sustain and enhance existing welfare barriers to <div style="font-size: 11.0413px; font-family: serif; left: 91.4551px; top: 493.892px; transform: rotate(0deg) scale(0.949411, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="134.8164023809433">the above mentioned services. <div style="font-size: 11.0413px; font-family: serif; left: 108.459px; top: 509.301px; transform: rotate(0deg) scale(0.965106, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="364.8099664427758">The first part of the paper explores the role of low status jobs in welfare ideas and <div style="font-size: 11.0413px; font-family: serif; left: 91.455px; top: 524.709px; transform: rotate(0deg) scale(0.957086, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="381.87720674419404">practices. The second part refers to the case of Albanian cleaners and Ukrainian carers <div style="font-size: 11.0413px; font-family: serif; left: 91.4544px; top: 540.118px; transform: rotate(0deg) scale(1.03556, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="382.1202067484856">working in Greece, their work conditions and values, and how both contribute to <div style="font-size: 11.0413px; font-family: serif; left: 91.4546px; top: 555.538px; transform: rotate(0deg) scale(0.94284, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_150_0" data-canvas-width="64.11312113227845">welfare limits.